The impact of exchange rate volatility on economic growth : a dynamic panel data analysis of Asian countries - Kong, Yin Hou (2004)
The issue of exchange rate volatility and its impact on economic performance has been the subject of numerous studies. However, the impact of exchange rate volatility on long-run economic growth remains an open question. The purpose of this project paper is to examine the impact of exchange rate volatility on economic growth in a panel of selected Asian Countries. Recent arguments on the relationship between exchange rate volatility and economic growth advanced by researchers into the literature of growth empirics are reviewed. Numerous measures of exchange ratevolatility that have been used in previous studies are considered and then quantified as a proxy for the empirical study. Based on an augmented growth model, the dynamic panel data regression model are estimated using four different estimation methods. Conditional upon other determinants, the results show that exchange rate volatility has a robust and significant negative impact on economic growth in Asian countries. This finding suggests that coordination of exchange rate policies directed to reduce exchange rate volatility in a group of countries is deemed to be desired. Specifically, the fixed exchange rate regimes such as common currency in a group of Asian countries may be worth considered seriously by policymakers.